2018
DOI: 10.1002/2017sw001803
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Worsening Particle Radiation Environment Observed by CRaTER and Implications for Future Human Deep‐Space Exploration

Abstract: Over the last decade, the solar wind has exhibited low densities and magnetic field strengths, representing anomalous states that have never been observed during the space age. As discussed by Schwadron, Blake, et al. (2014, https://doi.org/10.1002/2014SW001084), the cycle 23–24 solar activity led to the longest solar minimum in more than 80 years and continued into the “mini” solar maximum of cycle 24. During this weak activity, we observed galactic cosmic ray fluxes that exceeded theERobserved small solar en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 36 publications
(77 reference statements)
8
43
0
Order By: Relevance
“…The measurements from the westward‐viewing telescopes for EPEAD are shown here because they observe larger solar proton fluxes than the eastward view due to the former seeing particles whose gyro centers lie outside geosynchronous orbit and are hence less filtered by the geomagnetic field (e.g., Rodriguez et al, ). Several SEP enhancements are annotated by their cause, solar eruption (4, 6, and 10 September), or ICME1 or ICME2 energized (7 and 8, and 12 September), in agreement with the findings of Schwadron et al (, this special collection) through their analysis of the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) detector. The period 5–15 September elevated the risks of astronaut radiation, space hardware single‐event upsets, and high‐latitude trans‐ionospheric radio absorption.…”
Section: Sun To Earth: Solar Origins To Geospace Responsesupporting
confidence: 83%
“…The measurements from the westward‐viewing telescopes for EPEAD are shown here because they observe larger solar proton fluxes than the eastward view due to the former seeing particles whose gyro centers lie outside geosynchronous orbit and are hence less filtered by the geomagnetic field (e.g., Rodriguez et al, ). Several SEP enhancements are annotated by their cause, solar eruption (4, 6, and 10 September), or ICME1 or ICME2 energized (7 and 8, and 12 September), in agreement with the findings of Schwadron et al (, this special collection) through their analysis of the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) detector. The period 5–15 September elevated the risks of astronaut radiation, space hardware single‐event upsets, and high‐latitude trans‐ionospheric radio absorption.…”
Section: Sun To Earth: Solar Origins To Geospace Responsesupporting
confidence: 83%
“…This was the first SPE observed inside the ISS since May 2012, and in addition, it was an event which has been clearly seen by the CRaTER instrument orbiting Moon (Schwadron et al, ) and by the MSL‐RAD instrument on the surface of Mars where it contributed around 418 μGy in Si of additional dose. With all these instruments, we are now generating a unique data set for comparison of the (a) timeline of the event and (b) the influences of the event in terms of radiation limits for crews in LEO and for exploration missions.…”
Section: Discussionmentioning
confidence: 86%
“…Schwadron et al () concluded that the lens and skin dose on the surface of the Moon would approach the NASA 30‐day limits (see Table ); however, even moderate shielding would reduce the radiation dose below the limits.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…In the latter case, we expect to provide a further update, provided the LRO mission and CRaTER instrument continue nominal operations. Dosimetric results that include most of the same period reported here have been published elsewhere (Schwadron et al, ). CRaTER dose rate and LET data are also available online (see http://crater-web.sr.unh.edu/products.php).…”
Section: Introductionmentioning
confidence: 99%